A reference material for evaluating full-field out-of-plane deformation measurement system. (March 2023) - Long, Jun; Cai, Ping; Li, Kaiping; Guan, Wenqing; Pan, Shuyuan; Yan, Hao
Highlights: A circular plate reference material with submicron uncertainty is proposed. Proposed reference material provided an area for calibration rather than a point. Displacement of the centeral area can be traced to length standard. Standard uncertainty of full-field deformation of the reference materal is 0.015 μ m . Optical out-of-plane deformation system can be calibrated by the reference material. Abstract: Optical techniques such as Digital Speckle Pattern Interferometry(DSPI) and Digital Image Correlation (DIC) have been widely used in deformation measurement for their advantages of full-field, non-contact and high accuracy. To exploit the advantages of those optical techniques and enhance the confidence in the data from the optical system, a physical reference material (PRM) that can generate a deformation field with submicron uncertainty is proposed. The PRM is a circular plate of composite structure including a central rod and the peripheral annular plate clamped at the edge, , the central rod of which has merely displacement and no deformation under displacement loading. The displacement of the central area of the PRM is used for calibration, which provides connection to the national standard for length. Through traceability comparison, the expanded uncertainty of full field deformation of the PRM is 0.03 μ m, with a coverage factor of K = 2 . The PRM is used to calibrate a digital speckle pattern interferometry system. The combined standard uncertainty (CSU) of the full-field out-of-plane deformation measurement is 0.090 μ m . Both theoretical analysis and experiments results show that the proposed device can be applied as a PRM to calibrate and evaluate optical full-field out-of-plane deformation measurement system to a submicron level of uncertainty.